Strategic management of rural art museums in southern Zhejiang province, China: A mixed approach - Chenglong, Dai; Khiatthong, Thongchue (Edelweiss Applied Science and Technology, 2024)
Restoration of rural art museums in southern Zhejiang is important for regional and national development. Therefore, this study focuses on the strategic management issues of rural art museums in southern Zhejiang in the context of revitalization. This research sets three objectives: (1) to study and analyze rural art museums; (2) to synthesize strategic management; and (3) to create, propose, and define strategic management. This study used a mixed approach, with 300 stakeholders from five rural art museums in southern Zhejiang. The results show that elements of the strategic management model for rural art museums in southern Zhejiang Province can be determined. From the second objective, it is possible to formulate and implement a strategic management model in accordance with empirical data. An operational manual was developed and divided into 15 items for the strategic management of rural art museums that could be adapted to the southern region of Zhejiang Province. However, based on the questionnaires, in-depth interviews, and field visits, the average satisfaction with the level of rural art museum management was 3.27, with a standard deviation of 1.32. The average satisfaction score for the exhibition was 3.27 with a standard deviation of 1.38. Similarly, the average overall satisfaction with rural art museum was 3.4 with a standard deviation of 1.23. This study provides theoretical support and practical recommendations for strategic management of rural art museums. This study provides valuable insights into rural art museum research across the country. It also opens up new perspectives for the study of regional relations within the academic community and increases the depth and breadth of academic discussions.